MABÄá¸¥Iá¹¡ AL-ÄªMÄN â€˜ALÄ NAáº“RAH AHL AS-SUNNAH WA AL-JAMÄâ€™AH: DIRÄSAH â€˜AN MAKHá¹Å«á¹AH NAáº“M AL-WAá¹£IYYAH LI ASY-SYAIKH MUHAMMAD SAâ€™ID BONJOL AL-MÄ«NANGKÄBÄWÄ« - Hadi, Sofyan (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
-